2003
DOI: 10.1097/01.tp.0000047311.77702.59
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the antibodies involved in B-cell crossmatch positivity in renal transplantation

Abstract: These data suggest that in 77% of the patients, BCM positivity was not related with anti-HLA antibodies, and, in this case, graft survival was similar to that of the -BCM controls. In a minority of patients, anti-HLA class II antibodies were responsible for the +BCM, and their presence was associated with lower early, but not long-term, graft survival. Consequently, a +BCM should not systematically contraindicate kidney transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 23 publications
4
54
1
Order By: Relevance
“…In a previous study, we showed that positive BCXM in a population of 62 patients resulted from autoantibodies for 16% and donor-specific anti-HLA class II Abs for 23%, while 61% of cases remained unexplained (17). To assess whether AECA could explain some B cell reactivity, the presence of AECA was analyzed in regard to BCXM but regardless of immunization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we showed that positive BCXM in a population of 62 patients resulted from autoantibodies for 16% and donor-specific anti-HLA class II Abs for 23%, while 61% of cases remained unexplained (17). To assess whether AECA could explain some B cell reactivity, the presence of AECA was analyzed in regard to BCXM but regardless of immunization.…”
Section: Resultsmentioning
confidence: 99%
“…The control group included 25 non-HLA-immunized (PRA < 10%) patients, most of whom (21/25) had received a first transplant. Methods for the screening of anti-HLA immunization, autoantibodies and lymphocyte cross-matches have been previously reported (17). Briefly, donor and recipient HLA-A, B, DR and DQ typings were performed using a routine complement-dependent microlymphocytotoxicity (CDC) assay completed, when necessary, by polymerase chain reaction with sequence-specific primers (PCR-SSP: MicroSSP class II, One Lambda, Canoga Park, CA, USA) for the determination of HLA-DR or DQ alleles.…”
Section: Patients and Seramentioning
confidence: 99%
“…The main reason for the controversial outcomes in the literature is the lack of studies to confirm DSA. Le Bas-Bernardet et al (20) showed that only 23% of B cell cross-match-positive patients had DSA and demonstrated lower allograft survival, whereas cross-match-positive patients without DSA had similar graft survival to that of B cell cross-match-negative control subjects. Bray et al (21) showed that whereas patients with pretransplantation-positive FC cross-match and 0% FlowPRA had 100% 1-yr graft survival, it was only 40% in patients with both FC cross-match positivity and DSA by FlowPRA.…”
Section: Discussionmentioning
confidence: 99%
“…CLINICAL RESEARCH www.jasn.org bodies, and evidence would suggest that these antibodies correlate better with both morphologic and functional changes than do class I antibodies. [13][14][15][16][17] Other Possible Mechanisms in the Acceleration of Arteriosclerosis Persistently DSAϪ biopsies had increases in grade of arteriosclerosis, slower and not yet significant at 12 months, but highly significant for late biopsies (P ϭ 0.000006). The reasons for this increase are not clear.…”
Section: Role Of Dsa Positivitymentioning
confidence: 99%